Long-term effects of culture of preimplantation mouse embryos on behavior - Ecker, David J. (National Academy of Sciences, 2004)
Many procedures used in assisted reproductive technologies (ART) to treat human infertility entail culture of preimplantation embryos. Moreover, there is an increasing trend to culture embryos for longer periods of time before uterine transfer to identify the “best” embryos for transfer and to minimize multiple pregnancies. Embryo culture, however, can perturb embryo metabolism and gene expression, and the long-term consequences of culture are unknown. We have explored the behavioral consequences of embryo culture by using a 129S6/SvEvTac/C57BL/6J F(1) mouse model and find that adults derived from cultured embryos exhibit specific behavioral alterations in the elevated zero maze and Morris water maze tasks.